2009
DOI: 10.1242/dev.027193
|View full text |Cite
|
Sign up to set email alerts
|

The bHLH transcription factor Olig3 marks the dorsal neuroepithelium of the hindbrain and is essential for the development of brainstem nuclei

Abstract: The Olig3 gene encodes a bHLH factor that is expressed in the ventricular zone of the dorsal alar plate of the hindbrain. We found that the Olig3 + progenitor domain encompassed subdomains that co-expressed Math1, Ngn1, Mash1 and Ptf1a. Olig3 + cells give rise to neuronal types in the dorsal alar plate that we denote as class A neurons. We used genetic lineage tracing to demonstrate that class A neurons contribute to the nucleus of the solitary tract and to precerebellar nuclei. The fate of class A neurons was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
172
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 97 publications
(176 citation statements)
references
References 55 publications
4
172
0
Order By: Relevance
“…S4A′). We examined the status of Pou4f1/Brn3a, and its paralogue Pou4f2/Brn3b, broadly expressed in dorsal interneurons of the hindbrain and spinal cord (12,24) (Fig. S5).…”
Section: Change In Molecular Identity and Migration Of Nts Neurons Inmentioning
confidence: 99%
See 2 more Smart Citations
“…S4A′). We examined the status of Pou4f1/Brn3a, and its paralogue Pou4f2/Brn3b, broadly expressed in dorsal interneurons of the hindbrain and spinal cord (12,24) (Fig. S5).…”
Section: Change In Molecular Identity and Migration Of Nts Neurons Inmentioning
confidence: 99%
“…In the hindbrain, relay sensory neurons of the nTS are born from E9.5 to E13.5 (10) in the domain of dA3 progenitors, which extends from rhombomere (r) 4 to r7 (11,12) and switch on Phox2b postmitotically (9). In homozygous Phox2b null embryos, nTS precursors switch on Lmx1b and Rnx/Tlx3 and start migrating ventrally (9)-as they do in heterozygous or wild-type embryos (9,12).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…1A-D;Sieber et al, 2007). Some of these populations, such as dA4 and dB1, extend through rh2-7, while others, such as dA3, are present only in some rhombomeres (Sieber et al, 2007;Storm et al, 2009). In contrast to rh2-6, where dA/dB neurons arise throughout neurogenesis, in rh7, dBLa and dBLb neurons arise in a salt-and-pepper pattern from the dorsal VZ after E12 ( Fig.…”
Section: Introductionmentioning
confidence: 96%
“…1E; Sieber et al, 2007). Fate-mapping and gene expression studies identified dA3 cells as differentiating Lmx1b ϩ /Phox2b ϩ neurons of the nTS, dA4 cells of the caudal brainstem as newborn ION neurons, and dBLb cells as Lmx1b ϩ SpV neurons (Sieber et al, 2007;Storm et al, 2009;D'Autréaux et al, 2011), while the eventual fates of most other dA/dB populations, as well as dBLa cells, remain unknown.…”
Section: Introductionmentioning
confidence: 99%